To construct a derivation of the argument provided, we must show that from the premises provided, the conclusion R \lor T logically follows. Here are the premises and the conclusion listed:
1. P \lor \neg Q (premise)
2. P \to (V \land T) (premise)
3. (\neg V \lor \neg Q) \to T (premise)
4. R \lor T (conclusion to prove)
We can start the derivation as follows:
**Step 1: Assume P \lor \neg Q**
- Given as a premise.
**Step 2: Case 1 - Assume P**
- From Step 2, if P then V \land T, hence T is true.
- Therefore, R \lor T holds.
**Step 3: Case 2 - Assume \neg Q**
- From this assumption, consider \neg V \lor \neg Q, which is true.
- Applying the premise from Step 3, we get T is true.
- Therefore, R \lor T holds.
**Step 4: Conclusion R \lor T**
- In both cases, we have shown that T is true, making R \lor T true.
- Thus, by disjunction introduction, R \lor T is derived.
Therefore, the conclusion R \lor T logically follows from the given premises.
\boxed{R \lor T}